2021
DOI: 10.3233/thc-202766
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of CAD-CAM milled and printed complete dentures using computerized occlusal force analyser

Abstract: BACKGROUND: Digital complete dentures (CDs) by computer-aided designing and computer-aided manufacturing (CAD-CAM) techniques (milling and three-dimensional (3-D) printing) have been evaluated clinically and provided satisfactory results. But clinical studies assessing occlusal forces by digital dentures are lacking. OBJECTIVES: To compare the occlusal force parameters in complete dentures (CDs) fabricated by milling, 3-D printing and conventional techniques having 3 commonly used occlusal schemes, using compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…In addition, the results of the present study can be comparable to the results of Chaturvedi et al 2021b 55 who compared occlusal force analysis (percentage of occlusal force applied on the right and left sides of the arch difference between them, centralization of forces and percentage of maximum occlusal/bite force ) in complete dentures (CDs) fabricated by milling, 3-D printing and conventional techniques having 3 commonly used occlusal schemes, using computerized occlusal force analysis system (Tech-Scan III-T-Scan III), they concluded that the occlusal parameters in CDs were affected by the manufacturing techniques and occlusal schemes of CDs.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the results of the present study can be comparable to the results of Chaturvedi et al 2021b 55 who compared occlusal force analysis (percentage of occlusal force applied on the right and left sides of the arch difference between them, centralization of forces and percentage of maximum occlusal/bite force ) in complete dentures (CDs) fabricated by milling, 3-D printing and conventional techniques having 3 commonly used occlusal schemes, using computerized occlusal force analysis system (Tech-Scan III-T-Scan III), they concluded that the occlusal parameters in CDs were affected by the manufacturing techniques and occlusal schemes of CDs.…”
Section: Discussionsupporting
confidence: 92%
“…CECDs showed better retention of occlusal schemes. Bilateral balanced and lingualized occlusal schemes provided better centralization of forces, improved distribution, and high maximum occlusal forces [ 67 ]. This is important, as a significant relationship exists between the distribution of occlusal contacts and temporomandibular joint disorders (TMD) [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Digitally produced dentures seem to maintain the selected occlusal schemes better than conventionally produced ones [66]. However, the bond strength of denture teeth might be a concern with both CAM techniques [67].…”
Section: Comparing the Additive Vs The Subtractive Methodsmentioning
confidence: 99%
“…than conventionally produced ones [66]. However, the bond strength of denture teeth might be a concern with both CAM techniques [67].…”
Section: Case Reportmentioning
confidence: 99%